Values and the moral context of pastoral counseling - Ashby, Homer U. (Journal of religion and health, 1981)
This paper reviews the ways in which psychology has influenced the pastoral counseling movement, focuses, upon how the role and function of the pastoral counselor have lost their unique identity, and offers the construct of a moral context as a means for rediscovering, identifying, reviving, and strengthening the pastoral counselor's professional and spiritual selfimage.